(3GdUdGI GdHQjI aj GdUdGI Ydi NjQ GdHQjIs - (3GdHcQj, eUWai Hf ceGd GdOjf Hf Ydj, J(B1162(3g`s ((3YHO GdQMef Hf GHG jRjO GdHdjS GdTGaYjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj GNJUfG HSjO GdCfGe hHYO ajbhdeUWai GdUOjbj GdNdhJjhcfJ hVYJ bHd gPg GdUdhGJ UdhGJ SejJgG HGdOQ GdaGFb aCMHHJ Cf CLYd gPg CdaG dJchf dfG PNjQIs
(3BNQgG (B:s
(3hGdeYGaGJ GdOGFeI aj GdOjf hGdOfjG hGdBNQI Cfc Ydi cd TjA bOjQ hUdi Gddg Ydi SjOfG eMeO s
(3aj Chdg fbhd hagQS dYfGhjf GdQSGFd , haj BNQg CHjGJ TYQ aj GdJUha deUWai GdHcQj hfbhdG dGHf GdUdGMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 239s
(3eYLe GdeDdajf(B: 3 / 876s
(3EjVGM Gdecfhf(B: 2 / 69s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs